2009
DOI: 10.1080/17441690902930816
|View full text |Cite
|
Sign up to set email alerts
|

The provision of culturally specific care for victims of family violence in Aotearoa/New Zealand

Abstract: In this paper, I examine the diversity of opinions held by front-line family violence workers in Auckland, Aotearoa, on the issue of culturally specific care. Front-line workers are positioned at the interface between the system of services and benefits available from the state and the victims in need. In order to make sense of family violence discourses operating at the national level, I use front-line workers' perspectives to analyse the national frameworks for culturally specific care designed for Asian, Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…This paper has explored the perspectives and practices of social service providers and practitioners in Aotearoa/New Zealand who employ culturally grounded strategies in their work with minority ethnic women victims of domestic violence. It builds on and extends the work by scholars such as Haldane (2009) and Adelman et al (2012), who have identified the importance of mobilising culture in addressing issues of violence. In line with international research on domestic violence in ethnic minority communities (e.g.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…This paper has explored the perspectives and practices of social service providers and practitioners in Aotearoa/New Zealand who employ culturally grounded strategies in their work with minority ethnic women victims of domestic violence. It builds on and extends the work by scholars such as Haldane (2009) and Adelman et al (2012), who have identified the importance of mobilising culture in addressing issues of violence. In line with international research on domestic violence in ethnic minority communities (e.g.…”
Section: Discussionmentioning
confidence: 75%
“…Despite a much greater acknowledgement today of Māori and Pacific communities in social work responses to domestic violence (e.g. Haldane ), there is an absence of formal training that recognises other communities and their cultural realities. This paper thus points to the need for a detailed assessment and better codification of the culturally grounded strategies currently being used in an ad hoc manner by front‐line workers, and incorporating them within the training of practitioners who work in these communities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations